Model Pengembangan Media Poster dalam Pembelajaran Al-Qur’an Materi Surah al-Ma’un - Hidayat, Shabil Kurnia; Romadlon, Dzulfikar Akbar; Astutik, Anita Puji (Fitrah: Journal of Islamic Education, 2023)
Learning the Qur'an which is taught is often only through the lecture method without any supporting media which in turn has an impact on reducing student understanding. In this regard, SD Muhammadiyah 5 Porong has developed a media poster which aims to increase students' understanding of the interpretation of surah al-Ma'un relating to prayer. The focus of this research is on the development of poster media and its application in surah al-Ma'un material. This research uses research and development (R&D) method. This research was conducted at the elementary school level to conduct product trials and the application of the resulting media, namely in the form of posters on the importance of prayer after going through the validation stages. The data obtained in testing on a small scale with 6 student respondents fall into the eligible category. While the large-scale product trials involving 15 students, in total 97% of students said yes (Y) were interested in poster media when asked, while only 3% of students said they were not (T) interested in the very qualified category. This shows that the application of poster learning media to learning to interpret the interpretation of the Al-Qur'an juz 30 in the resulting surah al-Ma'un is categorized as very effective to apply to learning.